ASPEK KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG DALAM PEMBANGUNAN EKONOMI NASIONAL - Rizqi Muallif; Elfrida Ratnawati Gultom (LPPM Universitas Ekasakti Padang, 2023)
Economic and trade developments caused many debt problems in the community, followed by the monetary crisis that occurred in Indonesia, which had a negative impact on the national economy. Regarding the Debt Payment Obligation Postponement (“PKPU”) and bankruptcy, the case process has reached the highest number of up to 1,298 within one year. The number of PKPU processes is a serious concern considering that if this continues, the process of national economic recovery will take a long time. Law Number 37 of 2004 on Bankruptcy and Postponement of Debt Payment Obligation (“Bankruptcy and PKPU Law”) was established to meet the interests of the business world and to resolve debt problems effectively. The effectiveness of PKPU in preventing bankruptcy depends on the existence of good faith and a sense of cooperation (cooperative sense) from both the debtor and creditor so that the Reconciliation Plan can be negotiate and determined properly until the fulfillment of all debts is achieved. One example that has an impact when a company goes bankrupt is when the employees in the company that will be terminated will also have an impact on the state’s burden on the economy. The determination of the application of PKPU or bankruptcy declaration lies with the debtor who is expected to consider everything, especially the things that will have the most impact, including in the period of economic development in Indonesia. management and/or settlement of assets.